Association between Fibrinogen and Carotid Atherosclerosis According to Smoking Status in a Korean Male Population - Cho, Hye Min; Kang, Dae Ryong; Kim, Hyeon Chang; Oh, Sun Min; Kim, Byeong-Keuk; Suh, Il (Yonsei medical journal, 2015)
Although inconsistent, reports have shown fibrinogen levels to be associated with atherosclerosis. Accordingly, since cigarette smoking is associated with increased levels of fibrinogen and atherosclerosis, it may also affect the association between fibrinogen and atherosclerosis. We investigated the associations between fibrinogen and carotid intima-media thickness (IMT) according to smoking status in a Korean male population. Plasma fibrinogen levels were measured in 277 men aged 40-87 years without a history of myocardial infarction or stroke. High-resolution B-mode ultrasonography was used to examine the common carotid arteries. IMT level was analyzed both as a continuous (IMT-max, maximum value; IMT-tpm, 3-point mean value) and categorical variable (higher IMT; presence of plaque). Serial linear and logistic regression models were employed to examine the association between fibrinogen and IMT according to smoking status. Fibrinogen levels were positively associated with IMT-max (standardized β=0.25, p=0.021) and IMT-tpm (standardized β=0.21, p=0.038), even after adjusting for age, body mass index, systolic blood pressure, fasting glucose, and total cholesterol to high-density lipoprotein cholesterol ratio in current smokers (n=75). No significant association between fibrinogen and IMT, however, was noted in former smokers (n=80) or nonsmokers (n=122). Adjusted odds ratios (95% confidence interval) for having plaque per one standard deviation higher fibrinogen level were 2.06 (1.09-3.89) for current smokers, 0.68 (0.43-1.10) for former smokers, and 1.06 (0.60-1.87) for nonsmokers. Our findings suggest that cigarette smoking may modify the association between fibrinogen and carotid atherosclerosis. Further studies are required to confirm this finding in different populations.